E-068 Improving efficiency of acute ischemic stroke therapies: reducing door-to-needle and door-to-puncture time. (4th August 2020) - Chin, V; Yeboah, K; Balushi, A; Guthrie, A; Christopher, K; Edgell, R
Abstract : Introduction/Purpose: Early recanalization has been associated with a higher likelihood of favourable clinical outcome in acute ischemic stroke (AIS). It is imperative that stroke systems of care are set up to minimize workflow latencies that delay initiation of reperfusion therapies, i.e. IV tPA and mechanical thrombectomy (MT). Guidelines recommend a maximum door-to-needle (DTN) time of 60 minutes and a door-to-groin puncture time (DGPT) of 90 minutes in 50% of cases of large vessel occlusion (LVO). We aimed to evaluate various workflow latencies during stroke codes, including door-to-needle and door-to-groin puncture times, prior to and following initiation of internal quality improvement (QI) initiative at St Louis University Hospital (SLUH). Materials and Methods: All patients who received IV-tPA or MT at SLUH from December 2016 to May 2018 and July 2018 to December 2019 were included in this study and dichotomized into 'Pre-intervention' and 'Post-intervention' groups. Chart review data including patient demographics, arrival method, and risk factors were collected retrospectively. In addition, relevant times were collected which included time of ED arrival, time of NIHSS, time of CT acquisition, time of tPA bolus, time of groin puncture, and time of recanalization. NIHSS at discharge and complications of therapy were also collected. Results: For those receiving tPA, mean time to NIHSS was similar in the pre- and post-intervention groups, 4.28 minutes and 3.88 minutes, respectively (t=0.25, p=0.80); mean time to CT acquisition was also similar, 11.28 minutes and 12.53 minutes (t=-0.53, p=0.60). However, mean time for DTN decreased from 42.52 minutes to 33.87 minutes following the quality improvement initiative (t=2.29, p=0.02). tPA post-intervention patients were less likely to have asymptomatic ICH (χ 2 =6.22, p=0.01) and less likely to have other complications (χ 2 =4.66, p=0.03). For those receiving MT, mean time to NIHSS similar in both groups, 3.81 minutes compared to 5.55 minutes in the post-intervention group (t=-0.66, p=0.51); mean time to CT acquisition was 10.53 minutes compared to 12.23 minutes (t=-0.52, p=0.60). DGPT decreased from 101.81 minutes to 75.91 minutes (t=3.48, p=0.001) and mean time to recanalization decreased from 176.89 minutes to 109.74 minutes (t=6.68, p<0.001). In the MT group, no significant differences were found in complication rates between the pre- and post-intervention groups. Conclusion: Our internal QI Initiative to improve workflow latencies in the Code Stroke Protocol resulted in statistically significant reductions in DTN and DPGTs. Disclosures: V. Chin: None. K. Yeboah: 5; C; Saint Louis University. A. Balushi: None. A. Guthrie: 5; C; Saint Louis University. K. Christopher: 5; C; Saint Louis University. R. Edgell: 5; C; Saint Louis University.